Frequency of reported European ancestry among multiple sclerosis patients from four cities in the southern and southeastern regions of Brazil - Comini-Frota, Elizabeth Regina; Brum, Doralina Guimarães; Kaimen-Maciel, Damacio Ramon; Fragoso, Yara Dadalti; Barreira, Amilton Antunes; Donadi, Eduardo Antonio (Elsevier, 2013)
Recent reports on the prevalence of multiple sclerosis (MS) have described discrepancies between the rates in cities in the northeastern and southeastern regions of Brazil, representing a north-south gradient. European immigrants settled in southeastern and southern Brazil at the beginning of the twentieth century. In this study, we report the frequency of European ancestors among Brazilian MS patients in four cities in the southern and southeastern regions of Brazil. Methods: A total of 652 consecutive patients with confirmed MS diagnoses seen at four centers in Belo Horizonte, Ribeirão Preto, Londrina and Santos were asked about the origin of their ancestors, going back three generations. Results: 287 (44%) reported Italian ancestry, 211 (32%) reported that all ancestors were born in Brazil, 49 (7.5%) had Portuguese ancestry and 70 (10%) had Spanish ancestry. The patients in Belo Horizonte and Londrina reported higher proportions of Italian ancestry than the proportions estimated for the populations of their respective States. Conclusion: Brazil has a north-south gradient of 0.91/100,000 per degree of latitude, which is higher than the gradient for Latin America. Since the largest immigrant group that settled in southern and southeastern Brazil was from Italy, it is possible that Italian immigration was one of the factors that have contributed toward increasing the prevalence of MS in these regions. © 2013 Elsevier B.V. All rights reserved.
Keywords: Brazilian patients; Epidemiology; Immigration; Multiple sclerosis; Prevalence